"It`s this thing of being an Olympian that you don`t get from anything else": Changing experiences of Canadian individual-sport athletes with Olympic team selection - McEwen, C. E.; Hurd Clarke, L.; Bennett, E. V.; Dawson, K. A.; Crocker, P. R. E. (The Sport Psychologist, 2018)
The purpose of this study was to examine elite Canadian individual-sport athletes` experiences with an Olympic team-selection process. Six nonselected Canadian individual-sport athletes who were attempting to qualify for the Olympics took part in 3 semistructured interviews during the Olympic team-selection process, after they gained knowledge of their selection status, and after the Olympic Games. Data were analyzed using interpretative phenomenological analysis. Three major themes emerged from the interpretation of the athletes` experiences: (a) pursuing and expressing the Olympic athlete identity; (b) navigating the Olympic team-selection process: expectations, barriers, and tensions; and (c) moving on: reactions, life-goal reinvestment, and athletic-goal adjustment. Participants` experiences were shaped by personal motivation and social expectations, with changes shifting across the 3 interview periods. Athletes attempted to manage the discontent of nonselection through processes of positive reappraisal, athletic-goal adjustment, and accentuating other life goals and identities.